2005
DOI: 10.1021/ac048107i
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Adducts of Bovine Hemoglobin with Glutaraldehyde in a Hemoglobin-Based Oxygen Carrier

Abstract: Hemoglobin-based oxygen carriers (HBOCs) are being developed for the medical field, but because they could increase an athlete's performance, they are misapplied for doping purposes. We previously presented a screening method to detect Oxyglobin (Biopure Corp.) and PolyHeme (Northfield Laboratories Inc.) in serum samples using total acid hydrolysis followed by electrospray mass spectrometry analyses. An alternative mass spectrometric method involving enzymatic hydrolysis is here presented. Digestion of Oxyglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Additionally, the digestion of plasma samples with endoproteinase Glu-C followed by LC-MS/MS analysis with precursor ion scanning was used to identify Nterminal modifications of bovine Hb due to the use of crosslinking reagents. The peptide MLTAEE generated by enzymatic hydrolysis bears a modified amino function of the N-terminal methionine, which gives rise to precursor ions at m/z 759 and 761 to generate characteristic product ions at m/z 170 and 172, respectively, which are employed as target product and precursor ions in doping control assays (Gasthuys, Alves, & Tabet, 2005).…”
Section: Hemoglobin-based Oxygen Carriersmentioning
confidence: 99%
“…Additionally, the digestion of plasma samples with endoproteinase Glu-C followed by LC-MS/MS analysis with precursor ion scanning was used to identify Nterminal modifications of bovine Hb due to the use of crosslinking reagents. The peptide MLTAEE generated by enzymatic hydrolysis bears a modified amino function of the N-terminal methionine, which gives rise to precursor ions at m/z 759 and 761 to generate characteristic product ions at m/z 170 and 172, respectively, which are employed as target product and precursor ions in doping control assays (Gasthuys, Alves, & Tabet, 2005).…”
Section: Hemoglobin-based Oxygen Carriersmentioning
confidence: 99%
“…While distinct guidelines and so‐called identification points (IPs) have been defined for low molecular weight substances, LC/MS/MS is now being more widely used for peptide hormone and protein identification,6–13 necessitating rules for this class of compounds. The task of establishing identification criteria has been assigned to the accredited drug testing laboratories; hence, we discuss a set of criteria for target peptide and protein analysis from blood and urine in doping control specimens.…”
mentioning
confidence: 99%
“…Although scientific data about the effect of HBOCs on endurance and athletic performance is very limited and skepticism regarding a positive influence is prevalent (Schumacher et al, 2001;Schumacher and Ashenden, 2004), artificial oxygen carriers are considered relevant for doping controls. Numerous studies have been published demonstrating the determination of HBOCs in human plasma by means of various techniques such as 1D-gel electrophoresis , size-exclusion chromatography combined with UV detection (Gotzmann et al, 2002;VarletMarie et al, 2004) as well as different mass spectrometric approaches (Thevis et al, 2003;Gasthuys et al, 2004Gasthuys et al, , 2005Goebel et al, 2005 a,b). HBOCs are detectable in plasma specimens only; thus, all assays are based on blood sampling Fig.…”
Section: Hemoglobin-based Oxygen Carriers (Hbocs)mentioning
confidence: 99%
“…Tabet and co-workers (Gasthuys et al, 2004(Gasthuys et al, , 2005 suggested two different approaches to cope with bovine HBOCs such as Oxyglobin. The first has been based on acidic hydrolysis of serum samples followed by LC-MS/MS employing neutral loss scanning of 159 Da utilizing a triple quadrupole mass spectrometer.…”
Section: Hemoglobin-based Oxygen Carriers (Hbocs)mentioning
confidence: 99%